Identification of Characteristic Odorants in Duck Meat by Headspace-Gas Chromatography-Ion Mobility Spectrometry - ZHAO Gaiming, WANG Sen, ZHU Chaozhi, SUN Lingxia, WANG Zhuangzhuang, WANG Xinghui, XIE Wei (Shipin Kexue, 2023)
The characteristic odorants in duck breast, leg and clavicle meat cooked at 60 and 90 ℃ were analyzed by headspace gas chromatography-ion mobility spectrometry (HS-GC-IMS) and were identified by sensory evaluation, electronic nose measurement and flavor substance evaluation. The results showed that duck breast, leg and clavicle meat cooked at 90 ℃ had a stronger odor than at 60 ℃, and there were differences in the odor characteristics of different groups of duck meat samples, which was also confirmed by electronic nose analysis. A total of 61 volatile flavor compounds were identified by HS-GC-IMS. The types of volatile substances in different groups of duck meat samples were basically the same, but there were differences in their relative contents. Based on the sensory evaluation results and the relative odor activity values (ROAV) of flavor substances, a total of 12 characteristic odorants were identified, including nonanal, octanal, heptanal, decanal, pentanal, hexanal, (E)-2-octenal, (E)-2-heptenal, 2-methyl-butanal, 3-methyl-butanal, 2-heptanone and 1-octene-3-ol. The interaction between these substances contributed significantly to the formation of the odor of duck meat. Due to the differences in the types and contents of odorants, duck meat samples cooked at 60 and 90 ℃ had distinct odor characteristics.